Modelagem, análise e experimentação de sistema fotovoltaico isolado baseado em plataforma de simulação com diagrama de blocos. - Santos Junior, Francisco Antonio Ferreira dos (2016)
This paper presents a block diagram modeling of a grid-independent photovoltaic power generation system, including the steps of DC regulation, voltage inversion, and control system based on dynamic simulations in Simulink / Matlab® exclusively using the built-in blocks available in its library. A well-known technique in literature called MPPT (maximum power point tracking) was used for tracking the maximum power of the photovoltaic generation. However, the control that was used to maintain a constant output voltage of the Push-Pull is based on a method that is similar to the MPPT, which configures a novelty of this research. The integration of modeling the entire PV system with these control systems is carried out in Simulink for investigaton and production of simulation results. An experimental platform that includes an emulator of photovoltaic panels, a 1 kW Push-Pull converter, a three-phase inverter with three arms and a hydraulic load constituided by a motor-pump was built in the laboratory. The experimental results corroborate the methodology that was used.